The authoritarian specter - Altemeyer, Bob (Harvard University, 1996)
Introduction: Twenty stories Previous research on right-wing authoritarianism Studying authoritarianism: Research methodology and methodology research The personal origins of right-wing authoritarianism The cognitive behavior of authoritarians Inconsistency and blindness in the authoritarian mind Authoritarianism and religion Sex and the single authoritarian Dogmatism Left-wing authoritarianism The effects of hate literature The authoritarianism of legislators in North America Conclusion: A few last words on the subject